BUSINESS PLANNING BASED ON FINANCIAL STATEMENT PROJECTIONS AND FINANCIAL FEASIBILITY ANALYSIS AS A GROWTH STRATEGY FOR WAROENG CEMILAN AMIMI MSME (INTERNATIONAL SEMINAR, 2026)
This study aims to develop a business plan for Waroeng Cemilan Amimi, an MSME, based on financial statement projections and financial feasibility analysis to support strategic growth. The research adopts a quantitative case study approach, utilizing historical financial data and projecting future performance for the next five years. Financial feasibility is assessed using key indicators such as Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period to evaluate potential profitability and investment viability. The results indicate that a business planning approach grounded in financial projections can provide actionable insights for decision-making, optimize resource allocation, and enhance the growth potential of the MSME. Furthermore, the analysis highlights the importance of structured financial management and investment evaluation in small and medium enterprises. The findings offer practical guidance for business owners and managers in planning expansions, managing risks, and improving overall financial performance. This study contributes to the understanding of how financial planning and feasibility assessment can serve as critical tools for sustainable growth in the MSME sector.